Pain Intensity predicts Pain Catastrophizing during the Postpartum Period: A Longitudinal Random Intercept Cross-Lagged Panel study. - Román, Camila; Cumsille, Patricio; Gómez-Pérez, Lidia (Oxford University Press, 2021)
Objective. Pain catastrophizing is an important psychological predictor of pain. Recent evidence suggests the relationship between catastrophizing and pain intensity could be bidirectional, but most studies have been conducted on chronic pain patients and using criticized statistical methods. The present study aimed to examine if the relationship between pain intensity and catastrophizing was bidirectional in the context of childbirth. Methods. A total of 504 women without chronic pain were recruited on their 32–37 gestational week. They completed measures of catastrophizing and pain intensity on the first encounter and then again at 1, 3, and 6months postpartum. The temporal relationship between the variables was assessed using a random intercept crosslagged panel model. Results. The hypothesis of reciprocal association did not receive support, as pain intensity predicted catastrophizing during the postpartum period, but catastrophizing did not show an effect over pain intensity at any moment. Conclusions. Pain intensity predicting catastrophizing is consistent with previous literature, while the lack of effect of catastrophizing over pain intensity is an unexpected result, which may suggest that catastrophizing plays a different role in the postpartum period. These results highlight the importance of timely efforts for pain management during the postpartum period and contribute to the theoretical conceptualization of catastrophizing.
Keywords: Embarazo - Aspectos piscológicos; Dolor - Aspectos psicológicos; Puerperio; Análisis de datos de panel; Catastrophizing; Pain intensity; Pregnancy; Postpartum; Random intercept cross-lagged panel model